ACE gene polymorphism and erythropoietin in endurance athletes at moderate altitude - Gonzalez, A. J.; Hernandez, D.; de Vera, A.; Barrios, Y.; Salido, E.; Torres, A.; Terrados, N. (Medicine & Science in Sports & Exercise, 2006)
Purpose: To determine the role of the ACE (I/D) gene polymorphism on erythropoietic response in endurance athletes after natural exposure to moderate altitude.